Interpersonal Disgust, Ideological Orientations, and Dehumanization as Predictors of Intergroup Attitudes - Hodson, Gordon; Costello, Kimberly (Psychological Science, 2007)
Disgust is a basic emotion characterized by revulsion and rejection, yet it is relatively unexamined in the literature on prejudice. In the present investigation, interpersonal-disgust sensitivity (e.g., not wanting to wear clean used clothes or to sit on a warm seat vacated by a stranger) in particular predicted negative attitudes toward immigrants, foreigners, and socially deviant groups, even after controlling for concerns with contracting disease. The mechanisms underlying the link between interpersonal disgust and attitudes toward immigrants were explored using a path model. As predicted, the effect of interpersonal-disgust sensitivity on group attitudes was indirect, mediated by ideological orientations (social dominance orientation, right-wing authoritarianism) and dehumanizing perceptions of the out-group. The effects of social dominance orientation on group attitudes were both direct and indirect, via dehumanization. These results establish a link between disgust sensitivity and prejudice that is not accounted for by fear of infection, but rather is mediated by ideological orientations and dehumanizing group representations. Implications for understanding and reducing prejudice are discussed.